Mastering the digital transformation through organizational capabilities: A onceptual framework - Jens Konopik (Elsevier, 2022)
As digital transformation is changing entire industries, organizations are struggling to keep up with these changes. Scholars are viewing organizational capabilities as a central mean for organizations to master digital transformation. Based on a comprehensive literature review, this study identifies a broad set of relevant organizational capabilities and introduces a conceptual framework in which organizational capabilities are clustered into seven relevant themes for managing digital transformation. These capabilities are then embedded in the logic of the dynamic capability theory, highlighting the development of organizational capabilities throughout the digital transformation process. The results reveal that a differentiated perspective on the digital transformation process is beneficial to account for changing needs of organizational capabilities during the transformation process. Just as organizations themselves change during the process, various capabilities at different time points are needed to support and enable organizations during digital transformation. The developed conceptual framework gives organizations guidance for the development of organizational capabilities throughout the digital transformation process.